TRADISI PEMBACAAN SALAWAT NARIYAH DALAM MENJAGA RELIGIOSITAS MASYARAKAT SITUBONDO - Moh Hasan; Septiya Qur’ana (As-Syifa: Journal of Islamic Studies and History, 2026)
This study aims to examine the tradition of reciting Ṣalawat Nariyah and its important role in maintaining the religiosity of the Situbondo community. This phenomenon is interesting because this religious tradition not only functions as a worship practice but also has strong social and cultural significance in the lives of the local community. This study uses a descriptive-analytical method with a qualitative approach. Data was obtained through direct observation, interviews with religious and community leaders, and relevant literature studies. The results show that the tradition of reciting Ṣalawat Nariyah has become an integral part of the value system and religious practices of the Situbondo community. This tradition serves as a spiritual medium that strengthens faith, as well as a means of socialization and solidarity among residents. In addition, the recitation of Ṣalawat Nariyah also reinforces the Islamic identity of the Situbondo community and has become a symbol of social harmony in everyday life. Thus, this tradition needs to be preserved and developed as a religious and cultural heritage that contributes to the strengthening of religious values and togetherness in society.